Incidence of sperm antibodies before and after vasectomy. Issue 12 (December 1976) - Hunter, J; Logan, H; Greer, G
Abstract : Sperm-agglutinating antibodies were present in three (2-6%) of 117 fertile men and in 19 (33-9%) of 56 men who had been vasectomized. Twenty-four of the 56 vasectomized men had been studied before vasectomy; sperm-agglutinating antibodies were present in one (4-3%) compared with eight (33-3%) after vasectomy. No sperm-immobilizing antibodies were detected before vasectomy but were present in 10 (17-9%) of the 56 men after vasectomy.